Organocatalytic Michael Addition of Indoles to α‐Substituted Enals by Using a Diazepane Carboxylate Catalyst. Issue 18 (12th May 2017) - Larnaud, Florent; Sulpizi, Adamo; Häggman, Nicklas O.; Hughes, Jonathan M. E.; Dewez, Damien F.; Gleason, James L.
Abstract : The conjugate addition of indoles to α‐substituted enals is achieved by using a diazepane carboxylate catalyst under mild conditions (20 mol‐% catalyst, 20 mol‐% TFA, acetonitrile, –20 °C). The low basicity and high nucleophilicity of this catalyst overcomes the limitations of allylic 1, 3 strain in the intermediate iminium ions, which is normally observed with secondary‐amine catalysts. Conjugate addition of a series of substituted indoles as well as electron‐rich aromatics with a variety of α‐substituted enals is demonstrated. Abstract : Ethyl diazepane‐1‐carboxylate is highly effective in the formation of iminium ions from enals bearing α‐substituents. This cyclic hydrazine effectively catalyzes the addition of indoles and other electron‐rich aromatics to a series of α‐substituted enals in high yields under mild conditions.